Energetic cost of digging behavior in workers of the leaf-cutting ant Atta sexdens (Fabricius) - Camargo, Roberto Da Silva (2013)
Energetic cost of digging behavior in workers of the leaf-cutting ant Atta sexdens (Fabricius). During nest excavation, leaf-cutting ant workers undergo reduction in their body reserve, particularly carbohydrates. In order to estimate the energetic cost of digging, groups of 30 workers of the leaf-cutting ant Atta sexdens were sealed in a hermetic chamber for 24, 48 and 72 hours, with and without soil for digging, and had the CO2 concentration measured using respirometric chambers as well as volume of soil excavated (g). As expected, the worker groups that carried out soil excavation expelled more carbon dioxide than the groups that did not excavate. Therefore, a worker with body mass of 9.65 ± 1.50 mg dug in average 0.85 ± 0.27 g of soil for 24 hours, consuming ca. 0.58 ± 0.23 J. In this study, we calculate that the energetic cost of excavation per worker per day in the experimental set-up was ca. 0.58 J.